Pendampingan Peningkatan Imun Tubuh Melalui Aktifitas Fisik Bagi Lansia - Ibnu Andli Marta; Ade Zalindro; Nur Wisma (STKIP Andi Matappa, 2021)
Based on the reality that is currently sweeping the world, including Indonesia to West Sumatra, it is also exposed as a Red Zone area in the spread of Covid-19, as a sports practitioner, the writer feels the need to take part in helping the government and society in minimizing the spread of the virus. On this occasion, the servants will socialize, transfer knowledge, implement and assist the senior in physical activities. The focus of this service is to provide insights and skills in assisting the realization of physical activities for the seniors in Nagari Buayan, Batang Anai District, Padang Pariaman Regency. It is hoped that the realization of this activity will help break the chain of spread of the virus in West Sumatra, especially in Batang Anai District and anticipate the vulnerability of Corona Covid-19 virus transmission to the seniors in this area. The vulnerability of parents to disease is caused by decreased function of the body's immune system. One form of physical activity that is highly recommended to maintain the physical fitness of the senior is to do exercise for the seniors. The IPTEKS transfer carried out by the PKM Implementing Team is carried out at each stage using the principle that any innovation received should be through PIE (Preparation, Implementation and Evaluation). Data regarding the physical fitness of the seniors are presented in the form of descriptive analysis which shows that there is an increase in the physical fitness of the senior.